2007
DOI: 10.1021/ol070159h
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and General Approach to β-Functionalized Ketones

Abstract: The oxidation of selected anions (N 3 − , SCN − , I − and Br − ) by ceric ammonium nitrate (CAN) in the presence of substituted cyclopropyl alcohols provides a novel approach to β-functionalized ketones.The protocol has a number of advantages including short reaction times, ease of reagent handling and mild, neutral reaction conditions. Overall, this method provides an alternative pathway to important starting materials and intermediates in organic synthesis.Ketones substituted in the β position are important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(52 citation statements)
references
References 21 publications
1
50
0
1
Order By: Relevance
“…环丙醇可以用来合成多种化合物, 比如 β-取代的 酮 [10] 、烯丙基氯 [11] 、氮杂环 [12] 以及通过三元环开环的其 它化合物, 环丙醇可以被一些单电子氧化剂, 比如过硫 酸根和 Ag(I) [13] 、CAN [10] 、锰盐 [12] 等, 氧化开环形成 β-羰基碳自由基. 2013 年 Ilangovan 课题组 [14] 报道了一种 Ref.…”
unclassified
“…环丙醇可以用来合成多种化合物, 比如 β-取代的 酮 [10] 、烯丙基氯 [11] 、氮杂环 [12] 以及通过三元环开环的其 它化合物, 环丙醇可以被一些单电子氧化剂, 比如过硫 酸根和 Ag(I) [13] 、CAN [10] 、锰盐 [12] 等, 氧化开环形成 β-羰基碳自由基. 2013 年 Ilangovan 课题组 [14] 报道了一种 Ref.…”
unclassified
“…173 Recently, Flowers et al have shown that the selective oxidation of an inorganic anion in the presence of 1-substituted cyclopropanol and 1-substituted cyclobutanol led to the formation of b-and g-substituted ketones, respectively (Scheme 33). 174,175 The formation of b-substituted ketones was achieved using anions like SCN(À), N 3 (À) and halide while g-substituted ketones were obtained using halide ion. 175 The inorganic radical generated from the anion added to cyclopropanol leading to a radical intermediate, which on subsequent oxidation followed by deprotonation afforded the final product.…”
Section: Miscellaneous Transformationsmentioning
confidence: 99%
“…CAN has proven to be a cost-effective, versatile reagent that is capable of mediating novel carbon–carbon and carbon–heteroatom bonds 7,8. Previous research from our group has shown that β-substituted ketones are accessible through the use of CAN 9. By selectively oxidizing an inorganic anion in the presence of a 1-substituted cyclopropanol with CAN, the generated inorganic radical was added to the cyclopropanol resulting in ring opening.…”
Section: Introductionmentioning
confidence: 99%